Description of Subjective Welfare in Obese Student: Gambaran Kesejahteraan Subjektif pada Mahasiswi Obesitas - Putra, Aji Syailendra; Ansyah, Eko Hardi (Indonesian Journal of Innovation Studies, 2023)
Obesity is a condition of the body that has excess fat in the body, which can affect the subjective well-being of both subjects. This research will be conducted with the aim of describing subjective well-being to UMSIDA psychology students. There are 3 aspects that must be considered in subjective well-being, namely: positive affect, negative affect, and life satisfaction. This research uses phenomenological qualitative research methods, with a sample of 2 subjects with obesity who are studying at UMSIDA with psychology study program, the data collection technique that will be used is purposive sampling. The data collection technique used by the researcher is interviews. The result of the interview is that obesity has a different effect on the two subjects where for subject 1 obesity is bad luck for him, while for subject 2 obesity for him is only a body shape that can be changed and does not have a significant impact on the subject's subjective well-being.